COMPLICATIONS ASSOCIATED WITH REALIGNMENT OSTEOTOMY OF THE KNEE PERFORMED SIMULTANEOUSLY WITH ADDITIONAL RECONSTRUCTIVE PROCEDURES - Willey, Michael (The University of Iowa, 2010)
Debate remains regarding whether knee realignment osteotomy should be performed concomitantly with additional major knee reconstruction procedures or if it should be performed in a staged fashion. The purpose of this study is to analyze complications that occur when distal femoral osteotomy or high tibial osteotomy is performed concomitantly with other significant reconstructive procedures. Thirty-five patients with a minimum of one year follow up were identified. These patients underwent either high tibial or distal femoral osteotomy with concomitant significant additional knee reconstruction which included cartilage resurfacing requiring an arthrotomy, ligament reconstruction, meniscal transplantation, or extensor mechanism realignment requiring tibial tubercle osteotomy. Overall, 13/35 (37%) of these patients suffered at least one major or minor complication. Major complications occurred in 20.0% (7/35) and minor complications occurred in 25.7% (9/35). In conclusion, the rate of complication for combined osteotomy and reconstructive knee surgery is similar to that seen in cases of osteotomy done alone and combined surgery is advocated.